Using health impact assessment (HIA) to understand the wider health and well-being implications of policy decisions: the COVID-19 'staying at home and social distancing policy' in Wales - Liz Green; Kathryn Ashton; Sumina Azam; Mariana Dyakova; Timo Clemens; Mark A. Bellis (BMC, 2021)
Abstract Background Health Impact Assessment (HIA) is promoted as a decision-informing tool by public health and governmental agencies. HIA is beneficial when carried out as part of policy development but is also valuable as a methodology when a policy is being implemented to identify and understand the wider health and well-being impacts of policy decisions, particularly when a decision needs to be taken rapidly to protect the population. This paper focusses on a HIA of the 'Staying at Home and Social Distancing Policy' or 'lockdown' in response to the COVID-19 pandemic in Wales conducted by the Welsh national public health institute. It describes the process and findings, captures the learning and discusses how the process has been used to better understand the wider health and well-being impacts of policy decisions beyond direct health harm. It also examines the role of public health institutes in promoting and using HIA. Methods A HIA was conducted following a standard HIA five step process. A literature review was undertaken alongside 15 qualitative semi-structured interviews with key stakeholders, and relevant health and demographic data were collated. The results were triangulated and analysed to form a holistic assessment of the policy decision and its impacts. Results A wide range of major health and well-being impacts of the lockdown in Wales were identified across the determinants of health, which included positive and negative social, economic, environmental and mental well-being impacts beyond the impact on direct health. Populations affected included children and young people, those on low incomes and women as well as those whose health has been directly impacted by COVID-19 such as older people. The work highlighted the benefit that HIA can bring in emphasizing impacts which can inform policy and shared learning with others. Conclusion HIA is a largely underused tool to understand the impact of policy and political decisions, particularly when a decision has been taken at speed. This case study highlights how HIA provide evidence and information for advocacy and further work by public health institutes, health agencies and policy makers.